Demand of pregnancy in advanced age: A challenge to fertility specialists - Siddhartha Chatterjee (Wolters Kluwer Medknow Publications, 2016)
The couples of advanced age nowadays are requesting for the promotion of fertility for the first time quite more than what it was before. This is because of career making of men and women, increased divorce, and re-marriage. Physicians dealing with infertility problems are facing a lot of challenges in this regard. The diminished fecundity in advanced age is a routine happening. That is because of diminished ovarian reserve and there may be more aneuploidy in the oocytes or problem with the male gametes, so far as the genetic constitution, fertilizability, and motility are concerned. Research is going on all over the world in this regard, and the present way out is egg donation for elderly women with poor ovarian reserve. Though in a certain percentage of cases, in elderly women, natural conception is possible with or without ovulation induction, in males, usually fertility remain for long, even up to the advanced age, and reproductive assistance in the form of intracytoplasmic sperm injection is required with very poor sperm quality.